11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja (University of Maribor Press, 2025)
11th National Conference on Local Safety and Security: Local Safety and Security – Resilience of Local Communities to Security Risks. Conference proceedings comprise peer-reviewed papers presented at the 11th National Conference on Safety and Security in Local Communities, which took place in Maribor in November 2025. Safety and security in local communities remain the main topic of the conference, with a special focus of this year’s conference on the resilience of local communities to security risks. Papers present the result of the research programme »Safety and Security in Local Communities – Comparison of Rural and Urban Environments« of the Faculty of Criminal Justice and Security, University of Maribor and collaboration with practitioners from the police and local communities. Papers focus on various aspects of ensuring safety and security and the perception of threats in local communities, characteristics of crime, the role of schools in preventing peer violence, sustainable food supply, cooperation in protection and rescue in the event of natural disasters, the role of the police in ensuring security and cybersecurity. In addition, papers present examples of good practices.